Erratum for Supply chain strategies and international tax arbitrage. Issue 11 (13th November 2018) - Shunko, Masha; Do, Hung T.; Tsay, Andy A.
Abstract : This note corrects several typos in expressions and a sensitivity statement in Proposition 3 in Shunko et al. (2017 ).